Per- and Polyfluoroalkyl Substances and Breastfeeding as a Vulnerable Function: A Systematic Review of Epidemiological Studies - Amalie Timmermann; Oyemwenosa N. Avenbuan; Megan E. Romano; Joseph M. Braun; Janne S. Tolstrup; Laura N. Vandenberg; Suzanne E. Fenton (Toxics, 2023)
Milk formation in the breast during breastfeeding is a complex hormonally regulated process, potentially sensitive to the effects of endocrine-disrupting chemical exposures. The environmental chemicals, per- and polyfluoroalkyl substances (PFAS) are known endocrine disruptors. PFAS exposure have been associated with insufficient mammary gland development in mice and reduced breastfeeding duration in humans. The aim of this review was to gather the epidemiological evidence on the association between PFAS exposure and breastfeeding duration. Using PubMed and Embase, we performed a systematic literature search (on 23 January 2023) to identify epidemiological studies examining the association between maternal PFAS exposure and breastfeeding duration. Animal studies, reviews, and non-English studies were excluded. The risk of bias was assessed using the risk of bias in non-randomized studies of exposures tool. Estimates describing the association between PFAS exposure and the duration of breastfeeding were identified, and the data were synthesized separately for each type of PFAS and for the duration of exclusive and total breastfeeding. Six studies with between 336 and 2374 participants each were identified. PFAS exposure was assessed in serum samples (five studies) or based on residential address (one study). Five out of six studies found shorter total duration of breastfeeding with higher PFAS exposure. The most consistent associations were seen for perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and perfluorononanoic acid (PFNA). The finding of a potential causal association between PFAS exposure and breastfeeding duration is in agreement with findings from experimental studies.